SAT0488 Therapy-Induced Changes in Us-Detected Synovial Abnormalities in Juvenile Idiopathic Arthritis. (9th June 2015) - Lanni, S.; Ravelli, A.; Bovis, F.; Viola, S.; Magnaguagno, F.; Magnano, G.M.; Gandolfo, C.; Martini, A.; Malattia, C.
Abstract : Background: Over the last decade, the increasing application of ultrasound (US) in the pediatric rheumatology setting has enabled clinicians to visualize directly US synovial abnormalities of joints of patients with juvenile idiopathic arthritis (JIA). Intraarticular cortisteroid injections (IACI) in monotherapy or coupled with second-line medications are widely used in the management of children with JIA to induce relief of clinical symptoms and remission of synovitis. Objectives: The aim of the study was to investigate the ability of US to assess therapy-induced changes in US-detected synovial abnormalities of joints of children with JIA. Methods: Forty-one joints of 20 patients with JIA underwent at the study center clinical and US assessment at the IACI visit and at 6-month follow-up visit. Seven patients started a second-line drug at the time of the IACI. None of the patients had ongoing second-line treatments at the time of the IACI. Overall, 20 knees, 11 tibiotalar joints, 4 subtalar joints, 2 elbows and 4 wrists were examined. Tramcinolone exacetonide was used for all IACIs except for the subtalar joint where metilprednisolone acetate was the medication injected. For each joint, synovial hypertrophy (SH), joint effusion (JE) and power Doppler (PD) signal inside the area of synovitis were recorded and scored on a 4-point semi-quantitative scale. The US examinations were carried out by sonographers experienced in the assessment of children with chronic inflammatory arthritis who were blinded to clinical findings. Results: At follow-up visit 29/41 (71%) joints showed complete normalization on US of all 3 synovial abnormalities and 32/41 (78%) joints were in clinical remission. Total regression of all US abnormalities was observed in 10/11 (91%) tibiotalar joints, 12/20 (60%) knees, 1/4 (25%) subtalar joints, 2/2 (100%) elbows, and 4/4 (100%) wrists. Due to inefficacy of treatment 1 knee was reinjected before the follow-up visit. The remaining joints showed a partial decreasing in grading of US abnormalities. Seven/32 (22%) joints (5 knees and 2 subtalar joints) judged in remission on clinical grounds after 6 months from the therapeutic intervention showed residual US synovial abnormalities. Four/8 (50%) joints (2 tibiotalar joints, 1 knee and 1 wrist) with clinical active arthritis at follow-up visit did not displayed on US any of the 3 synovial abnormalities. Conclusions: A considerable proportion of joints shows improvement of US synovial abnormalities after starting treatment. US appears a useful additional tool to assess treatment response. The elbow, wrist and tibiotalar joint display the best therapy-induced changes in US-detected synovial abnormalities. Further longitudinal studies are warranted to understand whether residual subclinical synovitis may affect sustained therapy-induced remission in children with JIA. Disclosure of Interest: None declared